Restricted generosity in the New Testament - Murray, Timothy J. (2017)
This thesis is concerned with when, how and why the first Christians restricted their material generosity, according to the evidence of the New Testament texts. Its central argument is that restricted generosity in the early church was inseparable from the church’s self-conception as a fictive family. It is divided into two parts: the first discusses generosity, and its restrictions, in other first-century CE social structures (the oikos, voluntary associations and Jewish groups); the second turns to the New Testament itself.